Removal of microplastics in municipal sewage from China's largest water reclamation plant. (15th May 2019) - Yang, Libiao; Li, Kuixiao; Cui, Song; Kang, Yu; An, Lihui; Lei, Kun
Abstract: Municipal sewage treatment plants (STPs) are an important point source of microplastics in domestic waterways. In the present study, effluents from the largest water reclamation plant in China were sampled throughout the treatment process and microplastics were extracted and identified to evaluate their removal. As expected, microplastics were detected in the influent (12.03 ± 1.29 items/L). Following treatment, concentrations of microplastics were reduced by greater than 95% and 0.59 ± 0.22 items/L of microplastics were detected in reclaimed waters. Among detected microplastics, 18 types of polymers of ten colors were identified. Polyethylene terephthalate (PET), polystyrene (PS) and polypropylene (PP) accounted for greater than 70% of detected microplastics. Furthermore, microfibers were the dominant shape detected with an average size of 1110.72 ± 862.95 μm. However, microparticles accounted for only 14.08% of total microplastics with an average size of 681.46 ± 528.73 μm. Results of the present study suggest that current treatment technologies employed at the chosen STP are efficient to remove the majority of microplastics, however consideration of STPs as a point source of microplastics is important due to the large volumes of effluents being released into the aquatic environment on a consistent basis. Graphical abstract: Image 1 Highlights: Microplastics in influent and effluents from gSTP were studied. Existing sewage treatment processes remove microplastics effectively. PET, PS, and PP were the most prevalent microplastics in effluents. Microfiber was the main shape of microplastic in effluents. STPs is a point source of environmental microplastics.